If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
(1/6)*y = -2/5 // + -2/5
(1/6)*y-(-2/5) = 0
(1/6)*y+2/5 = 0
1/6*y+2/5 = 0 // - 2/5
1/6*y = -2/5 // : 1/6
y = -2/5/1/6
y = -12/5
y = -12/5
| 10.1+0.5p=0.9p+5.3 | | m+3m+8m= | | x+2/3=4/3 | | 7+2x+4=7 | | 26x+26000= | | x-3/2-1=x-4/3 | | 9x+13x= | | 4u-6/5 | | (y-5)(y+4)=-8 | | 34x=21+4x | | 2+5/7=-3 | | 3-4y+5=2y+12-4y | | y=0.5x^2-4x+12 | | 5=-13-3n | | x+0.4=2.8 | | -5x+8x=-3 | | 2y=2.5 | | 5x+6-7x=2-x+4 | | 5/8=b/63 | | -9=16 | | 8v=-6 | | 4(-2+x)=6-3x | | y=8/9x+5 | | -3(2+5x)=159 | | 3(+1)=3+3 | | 6-4=-8u+6u | | x^2+18x+27=-7 | | 4x+6(483-x)=2146 | | m^2-11m+30=0 | | 6a-6=63a+90 | | 3x+1=n | | 4x-x=-9 |